School as an adversary of democracy education (Pedagogical Horizons, 2025)
This article analyzes how the institution of school structurally counteracts democratic education. It reconstructs three core mechanisms of school socialization that conflict with the prerequisites of democratic participation: the internalization of authority-bound behavior, the promotion of competition and acceptance of inequality, and the systematic obstruction of socio-political judgment. Rather than preparing students for democratic life, schools serve to integrate them into hierarchically organized work structures.
Keywords: democracy education; school as institution; structures of authority; competition and inequality; socio-political judgment; critical theory of society